2020
DOI: 10.3390/sym12040587
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Dualism as an Instrument of Hierarchical Structure Formation in Molecular Biology

Abstract: The origin of chiral asymmetry in biology has attracted the attention of the research community throughout the years. In this paper we discuss the role of chirality and chirality sign alternation (L-D-L-D in proteins and D-L-D-L in DNA) in promoting self-organization in biology, starting at the level of single molecules and continuing to the level of supramolecular assemblies. In addition, we also discuss chiral assemblies in solutions of homochiral organic molecules. Sign-alternating chiral hierarchies create… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
19
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 54 publications
(74 reference statements)
1
19
0
1
Order By: Relevance
“…The helical pitch differs among the structural levels of cellulose organization due to the difference in their elements’ characteristic diameters. The twist direction sequentially changes when passing from the previous level to the next [ 45 ], caused by the energy gain provided by a decrease in the torsional stresses [ 46 , 47 , 48 ]. Due to the exponential dependence of the friction force on the number of turns in the coiled fiber, given by the Capstan equation, the supercoiled cellulose fibers cannot be disassembled without their untwisting [ 44 , 45 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…The helical pitch differs among the structural levels of cellulose organization due to the difference in their elements’ characteristic diameters. The twist direction sequentially changes when passing from the previous level to the next [ 45 ], caused by the energy gain provided by a decrease in the torsional stresses [ 46 , 47 , 48 ]. Due to the exponential dependence of the friction force on the number of turns in the coiled fiber, given by the Capstan equation, the supercoiled cellulose fibers cannot be disassembled without their untwisting [ 44 , 45 , 49 ].…”
Section: Introductionmentioning
confidence: 99%
“…Starting from the level of an asymmetric carbon atom in the amino acids of the primary structure of a protein and in DNA deoxyribose, we have earlier noted that there is a tendency to switch the chirality sign at the subsequent structural levels, resulting in a sequence of the type "left-handed"-"right-handed"-"left-handed"-"right-handed" in proteins ( Figure 1) and "right-handed"-"left-handed"-"right-handed"-"left-handed" in DNA [89][90][91]. The chirality sign alternates during the transition to higher-order structures of DNA structural and functional organization in A-and B-forms.…”
Section: Dnamentioning
confidence: 98%
“…The study of systems demonstrating a change in helicity sense is actively developing at present [92][93][94][95][96]. We mentioned earlier that the chirality of molecules or macroscopic objects is not a feature, but one of the general and fundamental structure-forming factors in both living and non-living nature [89][90][91]. On the other hand, it has been observed that artificially created homochiral systems may undergo the same process of spontaneous formation of hierarchies of molecular and supramolecular structures with an alternating chirality sign.…”
Section: Chiral Hierarchy Establishmentmentioning
confidence: 99%
“…Therefore, the interaction of the spin of the paramagnetic nucleus with the spins of the unpaired electrons can promote the singlet-triplet conversion that can even inhibit the reaction, as it was shown for 13 C dibenzyl ketone 26 . The same mechanism provides for the inhibition of the nucleic acid synthesis by paramagnetic ions, such as 25 Mg, 43 Ca, and 67 Zn 27 .…”
mentioning
confidence: 91%
“… The quasi-one-dimensional supramolecular strings spontaneously formed by TFAAS have a helical structure and organize into a complex hierarchy of the structural levels sequentially changing the sign of chirality 33 . Such an organization is peculiar for the biological macromolecules 36 , 43 and seems to be forced by the chirality itself. Moreover, formation of the strings by TFAAAs can be accompanied by the spontaneous resolution of the enatiomers 44 .…”
mentioning
confidence: 99%